Resultados de patologia clínica e dosagens de elementos minerais em bovinos acometidos pelo botulismo epizoótico no estado de são paulo - Lisbôa, Júlio Augusto N.; Kuchembuck, Marcio R. G.; Kohayagawa, Aguemi; Bomfim, Sueli R. M.; Santiago, Alcimir M. H.; Dutra, Iveraldo S. (My University, 1996)
In order to study laboratorial aspects of beef cow mortality, a syndrome popularly known as doença da vaca caída, examens were made of blood, cerebrospinal fluid, serum, bone and liver samples from 32 naturally affected 4 to 9 year old cows, 27 belonging to the Nellore breed and 5 were crossbred Nellore, all originating from farms located in municipalities near Botucatu, State of São Paulo. Laboratory determinations were analysed by descriptive statistics and included hematological values, total plasma protein, plasma fibrinogen, cerebrospinal fluid analysis, and concentration measurements of serum calcium, phosphorus, magnesium, sodium, potassium, chloride, total protein, albumin, globulin, alkaline phosphatase, aspartate aminotransferase, gama-glutamyltransferase and creatine kinase activities, included bone ash percentage and concentrations of calcium, phosphorus and magnesium, and also hepatic levels of copper, zinc, iron, manganese and cobalt. In addition, mouse bioassays and complement micro-fixation tests were performed to detect botulinum toxins in liver samples. The results indicated leukocytosis (13,3±3,9 x103/mm3) with neutrophilia (8,9±3,2 x103/mm3), hypocalcemia (7,8±1,7mg/dl), hypophosphatemia (3,6±1,6mg/dl), hypoalbuminemia (2,9±0,9g/dl), increased creatine kinase activity (691,0±829,7 UI/l), and reduced ash percentage (60,3±1,9%) and low phosphorus (17,2±0,4%) in bone. The other values were all within normal limits. The diagnosis of botulism, involving type C and D toxins, was confirmed as the cause of the mortality in the region of study, what is strongly consistent with the other laboratorial findings.
Clinical pathological data and analyses of mineral elements of cattle affected by epizootic botulism in the State of São Paulo
Keywords: Bovine; Epizootic botulism; Hematology; Mineral deficiency; Serum biochemistry